Pro Bono Legal Assistance at the Law Office of Riswanto Lasdin S.H., M.H., CLA and Partners to Ensure Access to Justice for Marginalized Communities in Palu City - Andini Cahya Pratiwi; Nurfatimah Azzahra (Abdi Masyarakat, 2026)
The implementation of pro bono legal aid by the Law Office of Riswanto Lasdin S.H., M.H., CLA and Partners in Palu City is an effort to realize access to justice for marginalized communities. Using empirical juridical methods and a sociological approach to law, this study analyzes the impacts, obstacles, and solutions in the implementation of pro bono legal aid. The results show that pro bono services provide a significant multidimensional impact for vulnerable groups, including casual daily laborers, traditional fishermen, street vendors, female heads of families, and victims of the 2018 Palu earthquake and tsunami. Pro bono legal aid not only serves as a cost-saving measure but also as a transformative instrument that shifts clients' position from passive legal subjects to active, dignified participants in the judicial process. However, its implementation still faces systemic obstacles, including legal gaps in Law Number 18 of 2003 concerning Advocates and Government Regulation Number 83 of 2008, a limited scope of services, weak sanction mechanisms, and low public awareness. This study recommends comprehensive regulatory reform, the development of a systematic referral network, the development of digital platforms, and participatory legal counseling as strategic steps in optimizing the implementation of pro bono to ensure the principle of Equality Before The Law for all levels of society.